Economic or Public Health? Southeast Asia’s Tackling of COVID-19 a Year Later - Arumsari, Imas; Fauzi, Ridhwan; Maruf, Mohammad Ainul; Bigwanto, Mouhamad (Kesmas, 2021)
The world has been challenged by rapidly spreading COVID-19 outbreaks for a year now. Southeast Asian countries have had different strategies to deal withthe pandemic. This review aimed to elaborate on Southeast Asian countries’ strategies in managing the trade-off between economic and public health, withfurther consideration of how such approaches were associated with the dynamics of the number of cases and the speed of economic recovery. This reviewevaluated the COVID-19 mitigation efforts spanning one year in the Southeast Asian (SEA) countries listed based on the Bloomberg COVID ResilienceRanking. As of May 24, 2021, three SEA countries (Thailand, Malaysia, and Indonesia) were chosen from the better (27th), moderate (35th), and worst (42nd)SEA country rankings. Peer-reviewed articles were obtained from Google Scholar and PubMed databases, and news articles were retrieved from GoogleNews. The data from government websites were also included. Sources were limited to those in the English and Indonesian languages that could be accessedbetween January 2020 and May 2021. Thailand, Malaysia, and Indonesia were found to have significantly prioritized consideration of the economy in handlingthe pandemic. Malaysia and Thailand had more stringent policies of imposing national lockdowns, while Indonesia had a partial lockdown. It was found thata weak pandemic response may result in substantial economic loss.